2017
DOI: 10.14701/ahbps.2017.21.1.30
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 gene polymorphism in acute biliary and non biliary pancreatitis: probable cause of high level parameters?

Abstract: Backgrounds/AimsInflammatory mediators of the innate immune response play fundamental roles in the pathogenesis of acute pancreatitis. The correlation between interleukin-8 (IL-8) gene polymorphism with types of acute pancreatitis and severity of pancreatitis, was evaluated in this study.MethodsAccording to the diagnostic criteria, 176 patients with acute pancreatitis were grouped into biliary (n=83) and nonbiliary pancreatitis (n=93). Healthy blood donors (n=100) served as controls. Serum alanine transaminase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In the initial screening process, a total of 178 articles were retrieved based on our selection strategy from the databases. After the removal of duplicated literatures and articles that did not meet the inclusion criteria, 10 studies involving 1646 AP patients and 1816 controls were finally included in this meta-analysis [19–28]. Of these selected studies, six studies were published in English [1921, 2426], three were published in Chinese [22, 27, 28], the other one was published in Russian [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial screening process, a total of 178 articles were retrieved based on our selection strategy from the databases. After the removal of duplicated literatures and articles that did not meet the inclusion criteria, 10 studies involving 1646 AP patients and 1816 controls were finally included in this meta-analysis [19–28]. Of these selected studies, six studies were published in English [1921, 2426], three were published in Chinese [22, 27, 28], the other one was published in Russian [23].…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicated literatures and articles that did not meet the inclusion criteria, 10 studies involving 1646 AP patients and 1816 controls were finally included in this meta-analysis [19–28]. Of these selected studies, six studies were published in English [1921, 2426], three were published in Chinese [22, 27, 28], the other one was published in Russian [23]. There were six studies conducted in China [20, 22, 24, 26–28], and one study conducted in U.S. [21], Russia [23], Turkey [19] and Hungary [25], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In one of the studies, heterozygous variants of IL-8 A/T mutation were more frequent in patients with severe AP, whereas a normal TT genotype was more often observed in patients with mild AP [29]. In turn, studies of IL-8 251A/T gene polymorphism in Chinese and Turkish populations did not show any significant correlations with the severity of the course of AP [30,31]. The researchers concluded that IL-8-251 gene polymorphism may be related with ethnic differences, which exert an effect on the results of studies [31].…”
Section: Acute and Chronic Pancreatitismentioning
confidence: 89%
“…The studies focused on genetic factors causing an increase in IL-8 during the inflammatory process. IL-8 plays a key role in the development of acute respiratory failure by activation of neutrophils, which is of basic importance for severe pancreatitis [30]. However, the results of these studies are unequivocal.…”
Section: Acute and Chronic Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation